A COMPARATIVE SEROEPIDEMIOLOGIC STUDY OF THE NEUTRALIZING ANTIBODY AGAINST THE VIRULENT STANDARD STRAINS AND THE SABIN VACCINE STRAINS OF POLIOVIRUS AMONG HEALTHY JAPANESE - OGINO, Toshio; YAMAZAKI, Shudo; IKEDA, Yoshifumi; TAKEDA, Naokazu; UTAGAWA, Etsuko; TANIMURA, Masako; MIYAMURA, Kikuko; HARA, Minoru (Japanese Journal of Medical Science and Biology, 1990)
The neutralizing antibody of 160 serum specimens collected in 1978 from healthy residents in five prefectures in Japan was titrated against both the virulent standard strains and the Sabin vaccine strains of three types of poliovirus. Antibody-positive rates with both strains of respective types at a level of 1: 4 were comparable in all three types of poliovirus. However, the geometric mean titers (GMTs) obtained against both strains showed statistically significant difference depending on the age-cohort's previous history of exposure to the wild or the vaccine strains of polioviruses: the younger age cohorts showed higher GMTs to the Sabin strains, while adults responded higher to the virulent standard strains. The difference was most pronounced in type 1.